Levels of serum and seminal fluid RANKL and osteoprotegerin in differentiating oligozoospermic and idiopathic infertile males: a case-control study - Layih, Osamah A.; Saleh, Basil O. (Reproduction and breeding, 2025)
Infertility is defined as the inability to conceive after one year of unprotected intercourse, with male factors accounting to about 50 % of cases. The study aimed to investigate the potential role of receptor activator of nuclear factor kappa-B ligand (RANKL) and osteoprotegerin (OPG) in differentiating between oligozoospemia and idiopathic subtypes of male infertility. A case-control study was conducted at the infertility center of Al-Batool Teaching Hospital in Diyala Governorate, Iraq, by the Department of Biochemistry, College of Medicine, University of Baghdad between April 2024 and January 2025. The study included 82 males, aged 20–55 years, divided into three groups based on seminal fluid analysis: 30 normozoospermic males (control group), 25 oligozoospermia patients, and 27 patients with idiopathic infertility. Serum and seminal fluid levels of (RANKL) and (OPG) were measured using enzyme-linked immunosorbent assays. Serum RANKL levels were significantly elevated in oligozoospermic patients (297.93 ± 85.99 pg/mL) compared to idiopathic infertility (147.16 ± 49.58 pg/mL) and normozoospermic controls (116.29 ± 20.95 pg/mL; p < 0.001). A similar pattern was observed in seminal RANKL levels, with oligozoospermia patients showing higher levels (402.39 ± 132.79 pg/mL) than controls (175.84 ± 24.46 pg/mL) (p < 0.001). In contrast, serum (OPG) levels were highest in normozoospermic controls (3.45 ± 0.98 ng/mL) and lowest in oligozoospermic patients (1.29 ± 0.56 ng/mL; p < 0.001). Seminal OPG exhibited the most pronounced differences, with controls (at 2.88 ± 0.89 ng/mL) compared to (1.00 ± 0.45 ng/mL) in oligozoospermic patients (p < 0.001). Reservoir operating characteristics (ROC) analysis demonstrated exceptional diagnostic utility for serum RANKL Area under the curve (AUC: 0.999) and OPG (AUC: 0.980) in differentiating oligozoospermia from normozoospermia. Serum RANKL showed 100 % sensitivity and 96.67 % specificity at a threshold >148.1 pg/mL, while OPG showed 100 % sensitivity and 92 % specificity at ≤2.2 ng/mL. For distinguishing idiopathic cases from normozoospermia, serum RANKL and OPG showed moderate diagnostic value (AUC 0.683 and 0.637). Seminal fluid measurements of both markers demonstrated moderate to excellent diagnostic performance for both comparisons. In conclusion, serum RANKL and OPG levels may serve as valuable biomarkers for differentiate between subtypes of male infertility.